Protocolo Interinstitucional de actuación conjunta en casos de abuso sexual infantil en la ciudad de Encarnación (Journal on studies and research of academic knowledge, 2014)
The present research about Sexual Abuse Intervention (ASI) protocol cases, pretends to be an effective tool in cases of existing facts of Child Sexual Abuse. While institutions have different functions assigned by law or their own protocols, it is necessary to have a single effective document to unify criteria and thereby prevent the victimization of those affected. Thus, we have used a methodology based on descriptive /explanatory study with a quantitative approach, also documentaries and field elements, so that the actions carried out are performed optimally and in coordination between the different institutions that are part of the circuit in of an ASI case intervention, avoiding the violation of the rights of children and adolescents.
Keywords: Child Sexual Abuse; victim; assailant; revictimization